Online printing shop system - Mohd Idzral Amzar, Rosli (2018)
In this study, an attempt has been made to study and develop the project of online printing shop system. The purpose of this system is to assist in reducing the problems on the store management and at the same time assisting customers or clients to facilitate the management of printing services. The Aim of this project is to develop an online system or program that use internet connection to submit the material and also at the same time design the material for print service. Methodology that has been use to develop the project is by using Rapid Application Development (RAD) which are more effective and organized that can help make this project develop work done. Therefore by creating the system also can help client or customer to reduce time consuming from going to shop and also help to design client project. In conclusion, by developing this project have many advantages that can help customer to get printing serviced anytime and anywhere without any problem regard time and cost saving.